The Effect of Special Exercises to Develop Some of the Variables and Basic Skills of the Young Basketball - Hasan Saleh Mahdi Al-Okbi (Journal of Global Pharma Technology, 2016)
The importance of research is reflected in the fact that it helps to detect the effect of aerobics and to know its efficacy with antioxidants that work to get rid of the free radicals causing fatigue to young basketball players. Researchers used the experimental approach to fit the nature of the problem on the players of the Sports Solidarity Club youth basketball season (2017-2018) (13), the comprehensive survey method was adopted in the selection of the sample and three players were identified for the purpose of conducting the exploratory experiment, reaching The final number of members of the main sample is (10) players. Through a gathering of data, most importantly, the exercises used, which were specialized exercises in the type of skill and complex exercises and skilled exercises for the speed of performance contributed to the development of some of the basic skills of basketball, for both the jump and high pituitary and chest handling and defensive movement, there was a direct impact of the effort in the proportions of salts in the body due to exposure to effort bodily led to fluid loss.Keywords: Physiological variables, Basic skills and basketball.